Some ethnocultural psychological features of the Kazakhs of the Republic of Kazakhstan - KIKBAEV, Daniar (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
An objective understanding of the psychological characteristics of a person is impossible outside the ethnocultural context. At the same time, cultural processes are constantly changing under the influence of various factors. These changes in culture affect the way people live and perceive reality. This review examines some ethnocultural psychological features of the Kazakhs of the Republic of Kazakhstan, including historical and cultural determinants of the psychology of modern Kazakhs; features of national stereotypes; the influence of national psychology on the interaction and behavior of people in organizations, and the specifics of the implementation of managerial functions by leaders; and the influence of national psychology on the behavior of Kazakhs in conflict situations.To achieve these goals, the issues of historical memory of the Kazakh people, ethnogenesis, as well as other factors that characterize the Kazakh mentality, are studied.Thus, the mentality of the people is dominated by hospitality, respect for older relatives, eloquence, the nomad cult, and tolerance. These features represent only a small part of Kazakh culture, which may differ depending on the region, social context, and characteristics of each representative of the ethnic group.Understanding the ethnocultural characteristics of Kazakhs contributes to effective cross-cultural interaction, communication, successful business and work, mutual respect, and tolerance. Furthermore, nowadays the need to study the ethnocultural psychological features of the Kazakh ethnic group is emphasized considering the military invasion of Russia in Ukraine.
Keywords: ethnocultural features of Kazakhs; psychology of Kazakhs; psychology of Kazakh behavior